If it's not what You are looking for type in the equation solver your own equation and let us solve it.
41/6-2x=x+23/6
We move all terms to the left:
41/6-2x-(x+23/6)=0
We add all the numbers together, and all the variables
-2x-(+x+23/6)+41/6=0
We get rid of parentheses
-2x-x-23/6+41/6=0
We multiply all the terms by the denominator
-2x*6-x*6-23+41=0
We add all the numbers together, and all the variables
-2x*6-x*6+18=0
Wy multiply elements
-12x-6x+18=0
We add all the numbers together, and all the variables
-18x+18=0
We move all terms containing x to the left, all other terms to the right
-18x=-18
x=-18/-18
x=1
| f+10+10f=9f-10 | | u+8+3u+1=98 | | -3(7r-8)=-28-8r | | 3t-4=3+4t | | 30+5y-30=y+99 | | 9d+8=-10+6d | | -4k+9=-3k | | 7t=-8+9t | | x+81+x+27=16x-47 | | 24-6x=-20+10x | | –5x+8=13 | | 15z-15=30 | | 9t+-8=7t | | 12y+27=39 | | k-10=3k | | -10w-2=-9-10 | | X+26+79+x=180 | | -8m=-7m-4 | | 3.5/n=6/48 | | 180=7x+11 | | 56-10b=6 | | 3-4(1-6x)=21+2x | | −5g+8g+3=−8g+8g+9 | | -2-2r=-3r | | b-4=5b | | 90/y-90/y-8=2/y | | 8m–5=3m–20 | | 6+2n=2n+6 | | 5x×10=20 | | s+90=7s-94 | | 2x−8=10 | | 7x–3=21–11 |